MOTIVASI BELAJAR SISWA MENGHIAS ALAS MEJA DENGAN SULAMAN FANTASI MELALUI DEMONSTRASI, LATIHAN, KERJA KELOMPOK DI SMPN I KEC.PAYAKUMBUH - Linda, Evie; Katin, Yusmar Emmy; Idrus, Yenni (Faculty of Tourism and Hospitality - Universitas Negeri Padang, 2012)
The purpose of the research to increase students learningmotivation with demonstration,exercises and teamwork todecorate linen with fantasy embroidery in developing of selfprogram at SMP N1 Kec.Payakumbuh. Kind of the research isclassroom action research consist of III cicles. In each ciclesprocess of learning consist of twice meeting. Students learningmotivation in the first cicles get 53%. In the second cicles get69%. In the third cicles get 85%. Subject of research consist ofstudents SMP N1 Kec.Payakumbuh amount 24 students.Technique of collect datas are observation, field record, analysisdatas as kuantitatif and kualitatif. The result of the researchincreate that students learning motivation the third cicles is 85percents, it means students learning motivation reached out fortarget which decided that is 80 percents. So demonstration,exercises and teamwork method of learning process can increasestudents learning motivation to decorate linen with fantasyembroidery.